The mantra of empowerment talk: an essay. Issue 3 (2nd July 2016) - Eliasoph, Nina
ABSTRACT: Projects around the world use the 'mantra of empowerment talk', calling for engagement that is civic, appreciative of local diversity, transformative, sustainably self-reliant, helpful for alleviating suffering, and transparent. These noble missions clash in everyday practice, so organizations that share the mantra also share predictable dilemmas. By gathering together studies of projects that share the mantra, and observing their typical efforts at resolving typical dilemmas, this article characterizes this newly prevalent organizational form: 'The empowerment project'. When one dilemma pops up here, immediately, another pops up elsewhere.